Sorafenib-Induced Liver Failure: A Case Report and Review of the Literature - Anneleen Van Hootegem; Chris Verslype; Werner Van Steenbergen (Case Reports in Hepatology)
In patients with hepatocellular carcinoma characterized by vascular invasion and/or extrahepatic disease, Sorafenib is considered treatment of choice. Although mild liver test abnormalities were reported in less than 1% of the patients in the two large randomized, controlled phase III trials, four cases of severe acute Sorafenib-induced hepatitis have been described. One of these four cases died from liver failure. In this paper, a patient with HCC with lung metastases developed high fever and a severe hepatitis that rapidly evolved into liver coma and death, two weeks after the initiation of Sorafenib. Biochemical parameters pointed to a hepatocellular type of injury. Clinical and biochemical presentations were compatible with a drug-induced hypersensitivity syndrome such as it has mainly been described for aromatic anticonvulsants, sulphonamides, and allopurinol. We hypothesize that an underlying cytochrome P450 dysfunction with the presence of reactive drug metabolites might lead to this potentially fatal Sorafenib-induced severe liver dysfunction.